Fast Food Work: An Empirical Perspective of Ideal Employees - M. Gould, Anthony (Relations industrielles / Industrial Relations, 2009)
SummaryThe McDonald’s labour management strategy is widespread in the fast food industry. Literature that is critical of the approach often portrays the work as low paid, unchallenging and uninteresting. Others argue that industry jobs provide an enhanced resume, training opportunities, and the possibility of a career. Rather than being inherently disadvantageous or beneficial, it is possible that fast food employment addresses the needs and aspirations of some more than others. This article proposes such a view in relation to teenagers. It poses the question: what are the characteristics of those who are suitable for industry work? Surveys are used to develop a statistical profile of ideal workers. Findings have implications for stakeholder decision making and offer an empirical perspective of a contentious issue that attracts opinion and speculation. Results indicate that developmental change and an overt inclination to choose a fast food career are key considerations in determining employee suitability.